Technologies used in vehicular networks for effective eco-friendly intelligent transportation system in smart cities - Mansour, Marvy Badr Monir; Barakat, Salma Mohamed (Edelweiss Applied Science and Technology, 2025)
Today, Vehicular Networks (VNs) can significantly improve the safety and sustainable growth of Intelligent Transportation Systems (ITSs) for smart cities. VNs offer efficient solutions to persistent urban problems such as congested roads and roadway safety. VNs adopt a wide range of technologies such as Vehicle-to-Vehicle (V2V), Vehicle-to-Infrastructure (V2I), and Vehicle-to-Everything (V2X) communications. These technologies allow cars to communicate with each other and with road infrastructure such as Roadside Units (RSUs) in real time, as well as enable the sharing of data. This can effectively mitigate accidents, enhance traffic flow, and minimize air pollution. Our paper extensively explores the state-of-the-art VN technologies used to establish safe and sustainable transportation systems. Additionally, our study highlights the importance of connectivity among automobiles for smarter urban environments to enhance transportation and support environmentally friendly growth. This is done by utilizing the Veins simulator in our work for conducting different mobility and traffic simulations. We formulate various scenarios, where we use the vehicles’ speed for our performance evaluation. Furthermore, we use OMNeT++ and SUMO for the accurate simulation of traffic motion in the city of Cairo, where results demonstrate that the speed of vehicles employing Vehicular Ad-Hoc Networks (VANETs) communications is not affected by traffic congestion.